The Geometric Design of Horizontal Alignment Using Indonesian Road Design Standard: A Case of Jalan Samarang â€“ Jalan Simirih STA 0+000 â€“ STA 0+715, Garut, West Java - Muhammad Rafi Zulfa Aryayuda; Usmanul Hayadi Umar (Fakultas Teknik Sipil dan Perencanaan, 2023)
Indonesia is a country that has many beautiful places that made Indonesia famous for the tourism industry. Connecting road between Jalan Samarang and Jalan Simirih is made to support residentsâ€™ economic activities as more tourists come. This research is purposed to design geometric roads, especially horizontal alignment according to â€œGuidelines For Road Geometric Design 2021â€. The road that will be made from STA 0+000 to STA 0+715 with objective data in 2022 using AutoCADÂ® 2D. This road planning uses quantitative data divided into primary and secondary data. The calculation can be concluded that on a 0,715 km road that uses Spiral-Spiral (SS) `